Pengembangan Sistem Informasi Kegiatan Pada Unit Pelaksana Teknis Pelatihan Teknis Perikanan Budidaya dan Pengolahan Produk Kelautan dan Perikanan Kepanjen Menggunakan Metode Rational Unified Process - Muhamad Yogi Saka F; Yusi Tyroni Mursityo; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The technical implementation unit for fisheries technical training in fisheries and processing of fisheries products (UPT PTPBP2KP) Kepanjen is one of the UPTs under the East Java provincial fisheries service, in this agency the guidance and training for fish farmers is expected to increase knowledge and skills. In general, the types of activities are divided into 2 types, namely training activities and monitoring and evaluation activities (MONEV). During the training and MONEV activities it takes more than 3 days because from the participant's search process to the creation of activity reports it still uses management documents in the form of hard copy and files in excel format. Based on this problem, the information system of training activities at UPT PTPBP2KP Kepanjen is needed using the Rational Unified Process (RUP) method to support and improve business processes. By using the RUP method, the problem solving process can work well because the iteration process can be repeated at the beginning to the end of the system development so that it can minimize errors in the needs of the system to be made. Later the results of this study are in the form of a website-based activity information system, from the developed system testing using 3 test methods namely black-box testing method that produces valid values ​​from each test item, compatibility testing method which results in minor issues and major issues in certain types of browsers, and the latest testing uses the user acceptance testing (UAT) method that produces a final assessment result of 93.4% or is very agreeable. Based on the results of these tests it can be concluded that the existence of information systems activities can improve and support business processes.